ANALIZING DENSITY AND ENVIRONMENTAL FACTORS OF THE JAVA SEA PELAGIC FISH USING CATCH, REMOTE SENSING, AND HYDRO ACOUSTIC DATA - Wijopriono Wijopriono (Research Center for Fisheries, 2007)
The relationship between the variations in density of pelagic fish in the Java Sea and a suite of variables describing the environment was studied. The indicator of density (local fish abundance) used were catch per unit of effort, obtained from 1,198 catches made by commercial fishing during the 5 year period (1998 until 2002), and number of fish per unit of area from acoustic investigation made in 2002.